The business of global energy transformation : saving billions through sustainable models - Larsson, Mats, 1963- (Palgrave Macmillan, 2012)
The large scale implementation of sustainable fuels and vehicle systems, in addition to green innovations in other areas will require sound business models. The nature and complexity of business opportunities differs widely between areas. This volume provides guidance for decision makers in business and politics regarding the business opportunities in various fields. It is one of the first books to analyze business and financial aspects of sustainable transport and fuel systems and it provides novel insights for researchers, managers, and politicians who work in energy and sustainability related areas. The transport systems of the future need to be well-structured and cost effective in order to compete against existing fuel and transport systems. The choice of technologies and the structure of systems will to a large extent determine the degree of success and the cost and investment needs. Only thorough analysis of the opportunities and business solutions can a foundation for success be created.